Antimicrobial Prophylaxis and Infection Control Precautions in Patients with Crush Injury - Balkan, İlker İnanç; Hakyemez, Fatma Sena (Cerrahpaşa Medical Journal, 2023)
The majority of infection-related deaths following earthquake injuries are caused by nosocomial infections, particularly in those receiving hemodialysis. Central venous catheter-related blood-stream infections, deep wound infections secondary to fasciotomy, and ventilator-associated pneumonias ranked as the top 3 causes of sepsis and mortality. Acinetobacter baumannii and Pseudomonas aeruginosa are among the leading causes. It is of vital importance to protect patients from nosocomial infections, who are rescued from rubble. Avoiding unnecessary fasciotomy, using appropriate empirical/pre-emptive antimicrobial therapy, ensuring full compliance with infection control measures, and referring patients to appropriate centers are all critical for decreasing mortality. All components of infection control program must be strictly adhered to, clinical samples and colonization scans of the patients should be followed dynamically and the treatment protocols should be modified according to culture results and local epidemiology. Whether the wound is closed or open, all crush injuries are regarded as tetanus-prone wounds. Tetanus prophylaxis (vaccine+immunoglobulin, if necessary) should be administered to all patients at risk. For patients with closed wounds, 24-hour prophylaxis is recommended. Ampicillinsulbactam is the best antibiotic for prophylaxis, with a potential coverage over environmental Acinetobacter strains. For patients with open wounds, all should be considered contaminated. Cultures (blood culture, wound culture, urine culture, and respiratory sample, if any) should be obtained after prompt wound cleaning and debridement. If the wound does not appear infected and cultures turn negative, a 5-day pre-emptive antibiotic therapy with ampicillin-sulbactam is sufficient. Cite this article as: Balkan İİ, Hakyemez FS. Antimicrobial prophylaxis and infection control precautions in patients with crush injury. Cerrahpaşa Med J. 2023;47(S1):38-41.